1985
DOI: 10.1080/00039896.1985.10545888
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Changes among Shipyard Painters Exposed to Solvents

Abstract: Painters in three shipyards, exposed to a wide variety of solvents, were examined. A short battery of performance tests, a detailed occupational history, and a special questionnaire to assess acute (prenarcotic, transitory) and chronic (persistent) neurologic symptoms was administered. The results of the neurobehavioral performance tests demonstrated decrements in central nervous system function in painters when compared with a control group matched for age, sex, race, and education. The prevalence of reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0
1

Year Published

1987
1987
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 11 publications
5
12
0
1
Order By: Relevance
“…The results of our study are consistent with the previous studies of Valciukas et al 22) and Ruijten et al 23) who reported neurobehavioral changes of shipyard painters. However, we can find no significant correlations between neurobehavioral performance and cumulative exposure index.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of our study are consistent with the previous studies of Valciukas et al 22) and Ruijten et al 23) who reported neurobehavioral changes of shipyard painters. However, we can find no significant correlations between neurobehavioral performance and cumulative exposure index.…”
Section: Discussionsupporting
confidence: 83%
“…The shipyard painters are exposed to many kinds of organic solvents and other neurotoxin such as lead which may be harmful to nervous system. In 1985 Valciukas et al 22) reported that neurobehavioral performance decreased in the shipyard painters compared with a control group, and found no significant correlations between performance test scores and duration of solvent exposure. In a study by Ruijten et al 23) , long-term exposure to xylene and other mixed organic solvents in shipyard spray painters caused impairment of simple visuo-motor performance and complex perceptual coding, and a relationship between effects on perceptual coding and the exposure index was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In workers from the paint industry [6] it was shown that signs of brain damage in the form of neurasthenic symptoms were significantly more common in the exposed workers, and that the severity of symptoms was dose-related. Identical findings were reported in another study [7]. Triebig [8] performed two epidemiological studies in painters.…”
supporting
confidence: 82%
“…Attentional processes were tested by Digit Span (Baker et al 1984), Digit Symbol (Matthews et al 1990), and Trail Making (Reitan 1958;Peters et al 1982;Valciukas et al 1985). Frontal executive functions were determined by the Verbal Fluency Test (animal; Goodglass and Kaplan 1983a, b;White et al 1990), Similarities (HaÈ nninen 1971;Baker et al 1984), and Trail Making B (White et al 1990Valciukas et al 1985). Learning and memory function were tested by the auditory-verbal learning test (AVLT) (Lezak 1983;Rey 1964) and Rey-Osterrieth Figure (Rey 1941;Osterrieth 1944;Lezak 1983).…”
Section: Neuropsychological Examinationmentioning
confidence: 99%
“…Neuropsychiatric symptoms associated with longterm exposure to organic solvents have been investigated for a long time (HaÈ nninen et al 1976;Elùfsson et al 1980;Gregersen et al 1984;Cherry et al 1985;Valciukas et al 1985;Fidler et al 1987;Maizlish et al 1987;van Vliet et al 1987;Triebig et al 1988Triebig et al , 1992aParkinson et al 1990;Bleecker et al 1991;Ford et al 1991;Spurgeon et al 1992;Daniell et al 1993;Ruijten et al 1994;Broadwell et al 1995;Escalona et al 1995;White et al 1995). It is generally accepted that chronic exposure to organic solvents can increase the prevalence of psychiatric symptomatology such as di culty in concentrating, memory impairment, fatigue, personality change, and dysphoric changes in mood.…”
Section: Introductionmentioning
confidence: 99%